Peran Optimisme Dalam Meningkatkan Subjective Well-Being Pada TNI Angkatan Udara - Derita Perhatian; Alimatus Sahrah (LPPM Universitas Proklamasi 45, 2022)
Work is a human activity both physically and mentally which is basically an innate which has a purpose in life for the individual who undertakes it, in this case whatever the field of work undertaken by an individual (both private and TNI workers) all must be lived and enjoyed in order to get happiness and satisfaction in life or better known as subjective well-being. The high or low subjective well-being felt by individuals, especially the Indonesian Air Force (AU) in the field of work, cannot be separated from the important role of optimism in individuals. This study aims to determine the role of optimism in increasing subjective well-being in the Indonesian Air Force (AU). The data were collected by spreading the optimism scale and the Likert scale type of subjective well-being with a total of 79 research subjects. The research method used is in the form of quantitative methods with product moment correlation analysis techniques and simple regression. The result of the product moment correlation analysis that have been carried out show that, there is a positive and significant relationship between optimism and subjective well-being as evidenced by the correlation coefficient value of 0.695 and p = 0.000 (p <0.01). It means that the higher the optimism, the higher subjective well-being. On the other hand, it also means that the lower the optimism, the lower the subjective well-being. Then, from the results of simple regression analysis, it is known that the magnitude of F = 0.696 and the correlation coefficient value R Square (R2) is 0.009 with sig. F table 0,000 (p <0.01). It means that optimism has an effective contribution of 0.9% in increasing subjective well-being to the Indonesian Air Force (AU).